GE_GERICHTE C/27994/2010 vom 6. März 2015 - GE Cour de justice (2015)
DIVORCE; OBLIGATION D'ENTRETIEN; ENFANT; MINORITÉ(ÂGE); MAJORITÉ(ÂGE); MINIMUM VITAL; REVENU HYPOTHÉTIQUE; DÉBUT | CC.133.1; CC.279.1; CC.285.1; CC.289.1